Missing money, missing policy and Resource Adequacy in Australia's National Electricity Market. (October 2019) - Simshauser, Paul
Abstract: From 2012 to 2017, 5000 MW of coal plant exited Australia's National Electricity Market (NEM) with an average notice period of just 5.2 months. Exit at-scale peaked just as imbalances in the market for natural gas emerged along with Renewable Energy entry lags due to policy discontinuity. By 2016–2017, the culmination of events produced more than 20 Lack of Reserve notices, two blackouts including a black system event, and forward prices at record levels. These conditions are traced to policy decisions a decade earlier. Lessons for other energy markets undergoing transformation include transparency over exit decisions, policy stability and limits to gas export capacity. Highlights: 5000 MW of coal plant exited Australia's NEM with an average notice of 5 months. Exit at-scale peaked just as imbalances emerged in the market for natural gas. Renewable investments were delayed due to policy discontinuity. The supply-side shock sent forward prices to record levels. Energy markets, typically well-designed for entry, also require an exit policy.